Thixotropic deformation behavior, rapid spheroidization and solid-liquid homogenization of semi-solid Al0.8Co0.5Cr1.5CuFeNi HEA with multilevel microstructure. (May 2023) - Huang, Minjie; Jiang, Jufu; Wang, Ying; Liu, Yingze; Zhang, Ying; Dong, Jian
Abstract: In this paper, powder metallurgy-rapid heating and isothermal-holding (PMRHI) method was proposed to realize the rapid spheroidization and suppression of solid grain coarsening in semi-solid Al0.8 Co1.5 Cr0.5 CuFeNi HEA. The thixotropic behavior and microstructure after PMRHI were investigated. Shear thinning effect exists during thixotropic deformation. The bimodal characteristics of flow stress degenerates with the proceeding of solid grain sliding (SS) and flow of liquid incorporating solid grains (FLS), indicating solid-liquid homogeneity and stable thixotropic deformation. The solid-liquid distribution homogeneity can suppress voids and hot tearing caused by liquid film channels. In multilevel semi-solid microstructure, the orientation relationship between solidified liquid phase and solid grain is approximately Kurdjumov-Sachs relationship, fine Al-Ni and Fe-Cr rich spinodal plates and nano Cu precipitates are formed in solid grain. The rapid spheroidization is realized due to initial dispersed powder metallurgy microstructure. After the steady thixotropic deformation of 1225 °C /0.05 s −1, mechanical properties were significantly improved. Graphical abstract: Image, graphical abstract